Narrative strategies in Crónica de músicos y diablos: Between the historiographical chronicle and the menippean satire - Montalvo Yamunaqué, Fernando (2019)
The purpose of this research paper is to provide a first look at the study of the narrative strategies which are present at Crónica de músicos y diablos (1991), one of Gregorio Martinez’s most remarkable novels. It is well known the interest of this author to regain the vital and social experience from popular classes of the Peruvian society, matter in which he has shown great sensitivity, an exuberant sensuality and a powerful sense of humor. We believe that, in Crónica de músicos y diablos , it can also be appreciated the novelist’s inclination to create a critical speech about the historiographical chronicle which it has traditionally been valued due to its capability to represent Peruvian foundation’s history. We think that Martinez’s novel builds a series of narrative strategies which are linked to this discursive genre in order to deeply question its mimetic capacity. Moreover the effective representation of the social reality that he offers it’s questioned because of its tendency to sustain itself on the vision of power’s subjects. For this paper we start from the theorical model designed by Mikhail Bakhtin which talks about the literary carnival and the menippean satire, concepts that are also contextualized for the Latin American literary reality by José Vilahomat. These  guidelines will be useful due to the fact that they suggest tips for interpreting noncanonical novels by analizing their structures.